2017
DOI: 10.1530/eje-17-0452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mitotane on the hypothalamic–pituitary–adrenal axis in patients with adrenocortical carcinoma

Abstract: The observation of lower ACTH levels in patients with ACC than that in patients with PAI, both in basal conditions and after CRH stimulation, suggests that mitotane may play an inhibitory effect on ACTH secretion at the pituitary levels. In conclusion, the present study shows that mitotane affects the HPA axis at multiple levels and no single biomarker may be used for the assessment of adrenal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Reduction of pituitary ACTH secretion by mitotane has been described previously as a potential etiology for HPA axis suppression. Reimondo et al found that mitotane-treated patients with adrenal insufficiency had lower ACTH levels than patients with primary adrenal insufficiency of other etiologies [15]. In our cohort, this finding was also present but not consistent among patients.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Reduction of pituitary ACTH secretion by mitotane has been described previously as a potential etiology for HPA axis suppression. Reimondo et al found that mitotane-treated patients with adrenal insufficiency had lower ACTH levels than patients with primary adrenal insufficiency of other etiologies [15]. In our cohort, this finding was also present but not consistent among patients.…”
Section: Discussioncontrasting
confidence: 64%
“…It also reduces adrenal steroidogenesis by inhibiting key mitochondrial enzymes like CYP11B, which reduces the conversion of hormone precursors into active hormones such as cortisol [11][12][13][14]. It was also found that mitotane could potentially interfere with pituitary function by comparing adrenocorticotropic hormone (ACTH) levels between patients treated with mitotane for ACC and patients with primary adrenal insufficiency (autoimmune or post-adrenalectomy) [15]. Basal values and post-CRH stimulation test (100 mcg) both showed a statistically significant decrease in ACTH levels in patients treated with mitotane, which suggests that this drug might have inhibitory effects at diverse levels of the hypothalamic-pituitary-adrenal (HPA) axis.…”
Section: Introductionmentioning
confidence: 99%
“…after 2-3 weeks or in case they experience adrenal insufficiency), because impairment of glucocorticoid effectiveness is rarely observed within the first few weeks. Due to the increased clearance and increased cortisol-binding globulin (268,270,271,272) with increasing mitotane plasma levels and based on clinical symptoms, the total hydrocortisone replacement dose will usually increased to a typical total daily dose of 50 mg in two or three divided doses. However, some patients require daily dosages up to 100 mg.…”
Section: R92 We Recommend Monitoring Of Blood Concentration Of Mitmentioning
confidence: 99%
“…However, some patients require daily dosages up to 100 mg. There is no reliable laboratory marker to guide the optimal dosage of hydrocortisone (271), which has to be based on clinical judgment similar to the management of patients with adrenal insufficiency (208). Mitotane-induced increase in cortisol-binding globulin may confound interpretation of serum cortisol measurement.…”
Section: R92 We Recommend Monitoring Of Blood Concentration Of Mitmentioning
confidence: 99%
“…Moreover, it may be of interest to evaluate the changes of 27OHC levels after mitotane exposition in other cell lines also, focusing on the endocrine glands other than adrenals (i.e., pituitary) that are affected by mitotane both in vitro [28,29] and in vivo [30,31].…”
Section: Discussionmentioning
confidence: 99%